10.18 Benzo[c]phospholes - Aitken,R. A. (Knowledge Updates 2022/2, 2022)
This chapter is a complete revision and update of the earlier Science of Synthesis contribution from 2000 describing methods for the synthesis of benzo[c]phospholes. A third of the references describe newer methods reported between 2000 and 2021 and several completely new approaches are included. Synthetic strategies for preparing these ring systems include metal-mediated reactions of 2,2′-bis(arylalkynyl)biaryls with phosphorus dihalides, reaction of ortho-disubstituted benzenes with phosphorus compounds, and aromatization of dihydrobenzo[c]phospholes.
Keywords: heterocycles; benzophospholes; phospholes; phosphorus compounds; ring closure; aromatization